Rethinking Distance Tutoring in e-Learning Environments: A Study of the Priority of Roles and Competencies of Open University Tutors in China - Li, Shuang; Zhang, Jingjing; Yu, Chen; Chen, Li (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2017)
This study aims to identify the priority of the roles and competencies of tutors working in the e-learning environments where the tutors are experiencing the changes brought by reforming traditional TV and broadcasting university to open universities. The mixed methods, DACUM, non-participatory observation, and questionnaires were used to identify the priority of the roles and competencies of tutors. The findings suggested that the priority of the roles and competencies has significantly changed accompanied to the shift of pedagogy from cognitive behaviorist to social-constructivist and connectivist. Changes in the roles of the instructional designer and instructor were highlighted. Significant differences in perceptions of the importance of the roles and competencies corresponding to learning management and technology use also merit further attention.